Pengembangan Sumber Belajar Berbasis VistaCreate dengan Pendekatan VCT di SMA Srijaya Negara Palembang: Development of Learning Resources using VistaCreate with VCT Approach - Sari, Silvia Eka; Pahlevi, Muhammad Reza; Safitri, Sani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
Learning resources are very useful in helping students understand learning materials. This research aims to develop learning video resources with the help of the VistaCreate website in History subjects. The research method used is R&D with the Allesi & Trollip model. The data collection techniques through interviews, questionnaires, and product trials, while data analysis techniques through data analysis from expert validation and analysis of learning outcomes. The research subjects were students of class XI IPS 4 SMA Srijaya Negara Palembang totaling 28 people. The results showed that in the implementation of the alpha test obtained a score of 4.92 material experts, 4.5 linguists, and 4.85 media experts, categorized as very valid. Then the beta test obtained a score of 4.75 from the individual trial and 4.61 from the small group test, categorized as very effective. The implementation of research in the field showed the results that the increase in students' abilities reached 61.43% and obtained an N-gain of 0.82 which was categorized as high. In this case, that the learning video resource is valid and effective to be used by students.